An empirical investigation of the extended Technology Acceptance Model to explain mobile banking adoption - Gokmenoglu, Korhan; Kaakeh, Mohamad (Univ Alexandru Ioan Cuza, Centrul Studii Europene, 2022)
This study utilizes partial least square-structural equation modelling to investigate the determinants of mobile banking adoption in the case of North Cyprus. The analysis was conducted on a sample of 250 respondents gathered through a self -administrated survey. We applied a modified Technology Acceptance Model (TAM) to the data. The findings showed that consumer innovativeness, perceived enjoyment, perceived ease of use, perceived reliability, and perceived usefulness have a significant positive relationship with the intention to use mobile banking services. Obtained evidence implies that bank managers should focus on developing mobile banking applications to meet the needs of the younger generation. Besides, banks are advised to introduce innovations in financial services offered through mobile banking to gain new customers.
Keywords: mobile banking; TAM; PLS-SEM; Northern Cyprus